Cryptographic Hardware and Embedded Systems " CHES 2000 : Second International Workshop Worcester, MA, USA, August 17 18, 2000 Proceedings - Koc Cetin K.; Paar, Christof (Lecture notes in computer science ;, 2000)
This book constitutes the thoroughly refereed post-proceedings of the Second International Workshop on Cryptographic Hardware and Embedded Systems, CHES 2000, held in Worcester, MA, USA in August 2000. The 25 revised full papers presented together with two invited contributions were carefully reviewed and selected from 51 submissions. The papers are organized in topical sections on implementation of elliptic curve cryptosystems, power and timing analysis attacks, hardware implementation of block ciphers, hardware architectures, power analysis attacks, arithmetic architectures, physical security and cryptanalysis, and new schemes and algorithms.